ANALYSIS OF THE INTERPRETATION OF THE CONCEPT “PROFESSIONAL IMAGE ”IN SCIENTIFIC LITERATURE (Pedagogy of Higher and Secondary Education, 2006)
The article is devoted to different approaches to the category “image ”, its main characteristics, types. The own notion of the term “the professional image” is considered.